'A level playing field': Young people's experiences of wheelchair basketball as an enabling place. (November 2019) - Bates, Laura; Kearns, Robin; Witten, Karen; Carroll, Penelope
Abstract: Using a novel case-study of a youth wheelchair basketball team in Auckland, New Zealand, we investigate the experiences of young people with physical disabilities in recreational sports places. We consider the 'enabling places' created by this sport, which can enhance disabled young people's wellbeing and social inclusion. Semi-structured interviews with the team's players and coordinators revealed logistical and societal challenges associated with facilitating youth-oriented sports, as well as those encountered by team members personally. They also identified physical health and social benefits experienced through involvement in wheelchair basketball. The material, social and affective dimensions of participants' experiences of wheelchair basketball elucidate the capacity for the sport, and its team members and settings, to affirm young people's identity and place-in-the-world. We conclude that youth-specific, inclusive sports generate enabling places that enhance young people's social inclusion, wellbeing and life enjoyment. Highlights: Youth-specific, inclusive sports places/teams enable social inclusion. Wheelchair basketball offers times and places affirming players' place-in-the-world. Team members encountered access/logistical challenges personally and as a team. Wheelchair basketball experience has material, social and affective dimensions. Youth wheelchair basketball creates enabling places that enhance wellbeing.